Diabetes Transitional Care from Inpatient to Outpatient Setting: Pharmacist Discharge Counseling. (April 2013) - Shah, Mansi; Norwood, CaTanya A.; Farias, Sol; Ibrahim, Sonia; Chong, Pang H.; Fogelfeld, Leon
Purpose: Diabetes transitional care from the inpatient to outpatient setting is understudied. This study evaluated the effect of inpatient pharmacist discharge counseling on outpatient diabetes medication adherence. Research methods: Prospective, randomized, controlled study compared pharmacist discharge counseling (intervention) with usual patient care (control) in 127 patients with established diabetes and an A1C ≥8% who had a provider and medications filled within the county health system. The primary outcome was diabetes medication adherence rate measured using the prescription of days covered (PDC) method. Results: Patients in the intervention, compared with control group, had greater diabetes medication adherence rate 150 days after discharge (55.2% vs 34.8%; P = .002), rate of follow-up visits (60.5% vs 43.9%; P = .01) and reduction in A1C (−1.97% vs +0.114%; P = .003). Being in the intervention group and having greater adherence with follow-up visits correlated independently with lower follow-up A1C. Conclusion: Transitional care in the form of inpatient education geared to improve self-management after hospital discharge. This may serve as a paradigm to improve outpatient adherence rate with medications, follow-up visits, and A1C reduction.